EFEKTIVITAS EDUKASI VIDEO DALAM UPAYA PENCEGAHAN DIARE PADA ANAK KELAS 3 MADRASAH HASYIM ASYARI PULOSARI TULUNGAGUNG - Aqlina, Dewi Shuwaibatul; Suryani, Pudji; Saputra, Dimas Dwi Yoga (Jurnal Pendidikan Kesehatan (e-Journal), 2022)
Diarrhea is a disease based on environment and hygiene. Therefore, there is a need for education that can accelerate the increase of knowledge effectively through electronic media, namely video. This study aims to determine changes in the level of knowledge about prevention of diarrhea in grade 3 children before and after education using video media. This study has a sample of 30 respondents in Madrasah Hasyim Asyari RT 02 RW 19 Pulosari Village, Ngunut District, Tulungagung Regency, the research was carried out on 18 and 20 March 2022. The research instrument used a questionnaire to examine data on diarrhea prevention, the data were analyzed using the Wilcoxon Singned Test. rank test. The results showed that the knowledge of respondents in the good category increased from 0 Percent before treatment to 100 Percent, while the knowledge of respondents in the moderate category decreased from 26.66 Percent before treatment to 0 Percent after treatment. The results of data analysis showed that there was an effectiveness of health education using video media on knowledge of diarrhea prevention in grade 3 children of Madrasah Hasyim Asyari, p value 0.00 which means there was an increase in knowledge of diarrhea prevention in children using video media. The conclusion is that there is an increase in children's knowledge about diarrhea prevention after attending education using video media. Video education media can be used as an alternative teaching material for teachers to students to improve health information